Hand Dermatitis Secondary to Exposure to Butternut Squash - Milaan A. Shah; Steven R. Feldman (Karger Publishers, 2022)
Cucurbita moschata, also known as butternut squash, is a common ingredient in numerous seasonal recipes but is an uncommon cause of cutaneous reactions. We present a 28-year-old male who developed dry and flaking skin of his right palm and fingers after coming in contact with butternut squash, which does not typically serve as an allergen that precipitates contact dermatitis. Given the unilateral localization of the dermatitis, timeline of the development of symptoms, and history of contact with butternut squash, the patient likely developed contact dermatitis of the right hand in response to exposure to butternut squash. Contact dermatitis with butternut squash appears to be an uncommon phenomenon, but it may occur more often and not be reported.